Conceptualizing death: How do children in Turkey understand death? - Bilge, Ayşe Reyyan; Öztürk, Rümeysa (Institute of Arts and Language Studies, 2021)
Death is a hard concept to understand and a delicate subject to talk about, especially with children. The primary purpose of the current study was to investigate the development of the death concept in children between the ages of 3-10. We also aimed to examine the influence of parental communication in the concept’s development. Fifty-four children (M = 6.44; 55.6% girls, 44.4 % boys) and their parents (N = 37; 6 fathers, 16.2%) were recruited. Children were interviewed one-on-one to evaluate their cognitive and emotional understanding of death. Moreover, their parents were administered a questionnaire to assess how they communicated the concept to their children. We found that older children (7-10 years) grasped some cognitive subcategories of death better than younger children (3-7 years). Our results also showed that both younger and older children had better cognitive and emotional comprehension of the concept if their parents have communicated it to them. These findings suggest that talking to children about death, in an age-appropriate way, helps them perceive the concept better. Age-appropriate communication, especially on an important topic such as death, can further be discussed in terms of social policy.

Ölüm, özellikle çocuklar için, anlaşılması zor bir kavram ve hassasiyetle konuşulması gereken bir konudur. Bu çalışmanın temel amacı 3-10 yaş aralığındaki çocuklarda ölüm kavramının gelişimini araştırmaktır. Kavramın gelişiminde, ayrıca ebeveynlerle çocuklar arasındaki iletişimin etkisi de incelenmiştir. Elli dört çocuk (Ort.: 6,44; 30 kız, 24 erkek) ve ebeveynleri (N=37; 6 baba, % 16.2) araştırmaya katılmıştır. Çocukların ölüm anlayışlarının bilişsel ve duygusal bileşenlerini değerlendirmek için birebir görüşmeler yapılmıştır. Ebeveynlerinden birine de ölüm kavramını çocuklarına nasıl ilettiklerini değerlendirmek için bir ölçek uygulanmıştır. Büyük çocukların (7-10 yaş) ölümün bilişsel alt kategorilerinden bazılarını küçük çocuklardan (3-7 yaş) daha iyi kavradığı bulunmuştur. Sonuçlar, ayrıca, ebeveynleriyle ölüm konusunu konuşmuş olan küçük ve büyük yaş gruplarındaki çocukların ölüm kavramını daha iyi anladıklarını göstermiştir. Bu bulgular, çocuklarla, yaş gruplarına uygun olarak, ölüm hakkında konuşmanın bu kavramı algılamaya yardımcı olduğunu göstermiştir. Yaşa uygun iletişim, özellikle ölüm gibi zor bir konuda çok önemli olup sosyal politikalar açısından değerlendirilmelidir.
Ölümü kavramsallaştırmak: Türkiye’deki çocuklar ölümü nasıl anlıyor?
Keywords: Children and Death; Death Concept; Development of Death Concept; Parental Communication; Çocuk ve Ölüm; Ölüm Kavramı; Ölüm Kavramının Gelişimi; Ebeveyn İletişimi